The Effect of Promotion Cost and The Fixed Price on Sales Level of The PT. Aston Inti Makmur - Nurfai Al Faizal Nurfai (Mulia Pratama, 2015)
Companies required to apply the concept of good management in marketing- to improved sales and compete with other companies. Management concept is not separated from what 4-p ( product, known as price, promotion, and fourth place ) where the element have a close relation to one another in supporting success in market a product. Writer conducted research on PT. Aston Inti Makmur prosperous by using the method library research and fieldwork namely, observation directly and an interview from sources that aims to see relations and promotional costs and influence between quotations against the sale or rent. The approach of theories such as multiple linear regression analysis, the correlation coefficient of linear regression analysis, the coefficient of multiple determination analysis, hypothesis t-test analysis and test hypotheses analysis F. With these it can be seen that the cost of promotion and pricing has a strong relationship between the cost of promotion and overall pricing on the level of sales at PT. Aston Inti Makmur. He method used is by way of qualitative analysis and quantitative analysis. Hen by using the formula yc = = b0 + b1x1 + b2x2 obtained calculation results are y c = -4,86 + 0,0050x1 + 0,0097x2. So based on this equation it can be concluded that the cost of promotion and pricing has a positive influence on the level of sales at PT Aston Inti Makmur respectively 0.0050 and 0.0097, and the analysis shows pricing has a greater influence compare with the cost promotion.